TAZ Is Highly Expressed in Gastric Signet Ring Cell Carcinoma. (24th February 2014) - Yue, Guofeng; Sun, Xia; Gimenez-Capitan, Ana; Shen, Jie; Yu, Lixia; Teixido, Cristina; Guan, Wenxian; Rosell, Rafael; Liu, Baorui; Wei, Jia
Abstract : Transcriptional coactivator with PDZ-binding motif ( TAZ ) is known to bind to a variety of transcription factors to control cell differentiation and organ development. We examined TAZ protein levels in 146 stage II–IV gastric cancer using immunohistochemistry (IHC), while TAZ mRNA was confirmed by quantitative reverse-transcription polymerase chain reaction (QRT-PCR) in 84 samples with enough tissue. TAZ protein expression was positive in 113 out of 146 (77.4%) gastric cancer samples. In parallel, TAZ mRNA expression was successfully detected in 81 of the 84 (96.4%) samples. Protein levels of TAZ were positively correlated with its mRNA levels (P = 0.018 ). High expression of TAZ protein was observed with higher percentage in gastric cancer samples with histology of signet ring cell carcinoma (SRCC) than adenocarcinoma (85.7% versus 60.2%, P = 0.001 ). Similarly, TAZ mRNA level was higher in SRCC than in adenocarcinoma (P = 0.003 ). When correlated with survival, the median overall survival (OS) is 14 months (95% CI: 12.2–15.8 months) in all patients. There was no significant association between survival and other clinical characteristics or TAZ expression levels. Our results show that TAZ is highly expressed in SRCC. TAZ might be considered as a target for the treatment of gastric SRCC in future.